Purification and Concentration of Influenza Types A and B by Chromatography on Calcium Phosphate - Lapidus, M. (1969)
A rapid chromatographic method for the isolation of types A and B influenza virus from allantoic fluid was described. The adsorbent was prepared from calcium dihydrogen orthophosphate monohydrate [Ca(H(2)PO(4))(2)·H(2)O] by alkali treatment. The addition of sodium trimetaphosphate to the influenza-infected allantoic fluid afforded a 67 to 100% viral recovery and a 26 to 43-fold increase in purity.